The Rise of the Rate of Profit During World War II - Dumenil, Gerard; Glick, Mark; Levy, Dominique (The Review of Economics and Statistics, 1993)
This study analyzes the important increase in the rate of profit which occurred in the United States during World War II. The gap between the predepression trend line, from 1900 to 1929, and the postwar line, from 1946 to 1989, is estimated as a shift of 15.8 percent in absolute terms (to be compared with an average of 29.0 percent over the whole period). Using a production function analysis, the authors demonstrate that this transformation can be explained by an acceleration in the rate of 'autonomous progress' between 1930 and 1945. They identify a sudden and nonneutral discontinuity in the process of technical change, characterized by an autonomous substitution of equipment for structures. Copyright 1993 by MIT Press.